A practical life based digital literacy framework for preservice teachers’ digital transformation - Uswatun Hasanah; Arpinda Syifa Awalin; Annas Ribab Sibilana; Miqdarul Khoir Syarofit (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The rapid digital transformation in preservice teacher education requires future teachers not only to use digital technologies but also to design innovative learning practices that address real-world educational needs. However, many programs still emphasize technical skills rather than the meaningful integration of digital competencies into authentic professional contexts. This study aims to examine how digital literacy is developed among preservice teachers in Islamic higher education institutions and to formulate a practical-life-based digital literacy framework to support their digital transformation. A qualitative multiple case study was conducted at two Indonesian Islamic universities. Data were collected through semi-structured interviews with faculty leaders and program administrators, analysis of curriculum documents, student digital portfolios, and observations of technology-enhanced learning environments. Data analysis followed an interactive model and thematic analysis supported by NVivo to ensure systematic coding and interpretation. The findings reveal that digital literacy development is shaped by institutional policy, curriculum integration, and practical-life-based learning activities, forming a digital ecosystem that transforms preservice teachers into innovative and reflective digital practitioners.